Penicillin Therapy in Children with Acute Rheumatic Fever: Side Effects, Malpractice and Anaphylactic Reactions - Murat Çiftel; Ayşe Süleyman; Halil Ertuğ (Güncel Pediatri)
Acute rheumatic fever (ARF) is more common in developing countries. ARF is a systemic disorder, which develops in children following group A streptococcal (GAS) pharyngitis. Rheumatic valvular disease is caused by autoimmune responses. Penicillin is used in the treatment of GAS tonsillopharyngitis and in primary and secondary prophylaxis against ARF. A single intramuscular (IM) injection of benzathine penicillin or oral penicillin V (phenoxymethylpenicillin) is administered as primary prophylaxis for 10 days. In the presence of rheumatic valvular disease, secondary prophylaxis with the injection of benzathine penicillin is required for life, or at least until the age of 40. IM injection of penicillin may cause fear and pain in children. Lidocaine or lidocaine-prilocaine (EMLA) creams can be used to decrease pain associated with IM injections. The most serious side effect of penicillin is, however, the anaphylactic reaction. This reaction can be caused by minor or major determinants of penicillin. Patients should be questioned about the past history of the penicillin allergy, and penicillin skin testing should be performed and interpreted appropriately in order to prevent anaphylactic reaction related to penicillin administration. In the presence of the suspicion of a penicillin allergy, skin testing should be avoided, and the patient should be tested by a pediatric allergy specialist using major and minor determinants to confirm a penicillin allergy. Patients who are allergic to penicillin can undergo desensitization in the absence of an alternative drug. It is a medical and legal obligation to perform and interpret the skin test appropriately, to keep the necessary equipment and drugs available for possible anaphylactic reactions, and to treat the patient appropriately in the case of an anaphylactic reaction. Penicillin is commonly used in pediatrics and pediatric cardiology.